2020
DOI: 10.1055/a-1079-5342
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Free Androgen as Predictors for Ovarian Hyperstimulation Syndrome in Non-PCOS Women

Abstract: We evaluated the effect of insulin resistance and free androgen index (FAI) in non-PCOS (polycystic ovary syndrome) infertile women following controlled ovarian hyperstimulation. A prospective study was done on 144 infertile non-PCOS women with regular menstrual cycle. At first, insulin resistance (IR), free androgen index (FAI), PCOM (polycystic ovary morphology), AFC (antral follicle count), and AMH (anti-Müllerian hormone) were assessed. The patients underwent assisted reproductive technology (ART), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…There was also a significant correlation between the level of AMH and the number of retrieved oocytes and embryos. In a recent study it was shown that AMH is a main predictor of OHSS in non-PCOS patients [13]. Moreover, Chen and colleagues have also shown there is a positive correlation between AMH and fertility rate, embryo quality, and oocyte number [14].…”
Section: Discussionmentioning
confidence: 97%
“…There was also a significant correlation between the level of AMH and the number of retrieved oocytes and embryos. In a recent study it was shown that AMH is a main predictor of OHSS in non-PCOS patients [13]. Moreover, Chen and colleagues have also shown there is a positive correlation between AMH and fertility rate, embryo quality, and oocyte number [14].…”
Section: Discussionmentioning
confidence: 97%
“…Both the basal serum AMH level (odds ratio, 1.7856; P = 0.0003) and serum E2 level on the day of hCG injection administration (odds ratio, 1.0005; P = 0.0455) proved to be significant predictors of OHSS by logistic regression analysis (9). Furthermore, some studies have demonstrated that the high risk factors associated with OHSS mainly include (6,14): (1) 6) having a history of OHSS (15,16). Studies have also shown that multiple follicles developed at the same time during the ovulation induction cycle, higher number of eggs obtained in the ART cycle and higher doses of exogenous human chorionic gonadotropin administration during the ovulation induction cycle, as well as pregnancy, may lead to an increased risk of OHSS (17).…”
Section: Discussionmentioning
confidence: 97%
“…Patients selection and inclusion criteria were according to the Rotterdam criteria, at least possessing two of the following three criterions can be defined as PCOS: (1) rare ovulation or chronic anovulation; (2) having hyperandrogenemia or hiperandrogen clinical manifestation; (3) demonstrating polycystic ovarian changes by ultrasound determination and exclusion of other etiologies (4,6). Patients with the following exclusion criteria were included: IVF/ICSI contraindications, uterine malformations, chromosomal abnormalities, rheumatic immune system diseases, untreated endometrial lesions, drug allergies, severe mental system diseases, pituitary tumors, congenital diseases, and abnormalities of blood glucose, blood pressure, thyroid function, prolactin, and so on.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the response of granulosa cells to FSH during the gonadotropin-dependent stage of folliculogenesis can be enhanced by insulin growth factors ( 27 ). Therefore, in the IVF setting, the risk of developing multifolliculogenesis or ovarian hyperstimulation syndrome to exogenous gonadotropin stimulation is higher in IR than non-IR patients ( 28 ).…”
Section: Discussionmentioning
confidence: 99%